Physical Activity Levels, Enjoyment, and Perceptions of Barriers to Physical Activity of Adolescents with Visual Impairments in Turkey - (:unkn) unknown (SAGE PUBLICATIONS INC, 2020)
Purpose: The purpose of this study is to determine the physical activity (PA) status of adolescents with visual impairment, their enjoyment of the PA, and their perception of barriers to PA. Design and Methods: This descriptive study was conducted with 110 adolescents with visual impairment. The data collection tools consisted of the (ALP-R2)-Physical Activity Subscale, the Physical Activity Enjoyment Scale (PAES), Barriers to Physical Activity Questionnaires, and an Observation Form. The data were analyzed using frequencies, correlation, and Kappa tests. Results: It was observed that 60% of the participants stated that they did not engage in PA, 58.2% said they did not engage in PA to the extent of breaking out in a sweat and increasing their heartbeat, and 48.2% indicated that they never did PA 3 times a week for 20 minutes or more. The PAES mean score was 55.1 +/- 5.5; the Physical Activity Subscale mean score was 12.5 +/- 4.1 (r = 0.42; p < 0.0 1 ). Discussion: Our findings were consistent with the results of other studies in that the changeable external factors and parental attitudes perceived as obstacles were similar. Implications for practitioners: Most of the participants wanted to be more active. Most of the adolescents' answers to the questions about the perceived barriers to PA were contrary to what had been expected. Although the adolescents said they did not engage in PA, the number of adolescents who perceived changeable factors such as the environment and parents' attitudes as barriers was not negligible.
Keywords: adolescent; visually impaired; physical activity; nursing